Attitude toward environmental protection and toward nature: How do they shape consumer behaviour for a sustainable tomato?. (June 2021) - Baldi, Lucia; Trentinaglia, Maria Teresa; Mancuso, Teresina; Peri, Massimo
Highlights: A methodological framework never adopted in the food consumption domain is used. We implement the Campbell Paradigm and related advancements on attitude measures. Attitude toward environmental protection and toward nature appreciation should be kept apart. Psycho-attitudinal propensity towards environmental issues affect differently consumer WTP. The way attitudes impact WTP for a sustainable tomato is also country-specific. Abstract: Several research efforts have tried to explain the forces driving food-related decisions. In this article, we explore how individual attitude toward the environment could be a potential determinant of green behavior. This research offers an original methodological framework never adopted in the food consumption domain that is based on the contribution of Campbell Paradigm and the related advancements on attitude measures proposed by the environmental psychology literature. We also contribute to the literature by envisaging a two-dimensional environmental attitude, that distinguishes between attitude toward environmental protection and toward nature appreciation. The ultimate target is to explain consumer purchasing intentions, represented by Willingness to Pay, toward a hypothetical tomato with improved resource use efficiency taking into account consumer psycho-attitudinal propensity towards environmental issues. The analysis is conducted in Italy and in the UK, two countries characterized by different perceptions about tomato as a consumption good and about water related issues. Findings indicate that the two dimensions of consumer attitude affect differently the spending propensity for a sustainable tomato and these differences are also country-specific. The analysis suggests that policies aimed at promoting sustainable food products should also target the consumer type (naturalist or environmentalist) that is more sensible to environmental sustainability.